Characteristics of the second stage of evaporation and water redistribution through double layered sandy soil profiles - A. Alowaisy; N. Yasufuku (International Association of Lowland Technology, 2018)
Evaporation from porous media involves a complex pore scale water and vapor transportation that directly affects the liquid phase distribution and fluxes. The presence of textural contrast boundary in multilayered profiles adds to the complexity. This study aims at evaluating the textural contrast boundary depth and individual layer thickness influence on the actual evaporation and water storage through double-layered soil profiles. For coarse overlying fine sand, it was found that the top layer small capillaries contribute to the majority of water lost through the falling rate stage. Considering fine overlying coarse sand profiles, the pumping phenomenon from the bottom coarse layer to the top fine layer occurs before the arrival of the drying front to the textural boundary due to the increasing suction forces within the top fine layer. The water storage capability of double layered soil profiles depends highly on the top to the bottom small capillaries ratio multiplied by the layer thickness ratio. Regardless the atmospheric conditions and layering sequence, it was concluded that the shallower the textural contrast boundary results in decreasing the total duration required to achieve the residual evaporation stage thus leads to higher water storage capabilities through the first and second evaporation stages.